Delivering home-based services : a social work perspective - Allen, Susan F., 1951-; Tracy, Elizabeth M. (Columbia University Press, 2009)
Service providers are increasingly called upon to serve clients at home, a setting even a seasoned professional can find difficult to negotiate. From monitoring the health of older populations to managing paroled offenders, preventing child abuse, and reunifying families, home-based services require models that ensure positive outcomes and address the ethical dilemmas that might arise in such sensitive contexts. The contributors to this volume are national experts in diverse fields of social work practice, policy, and research. Treating the home as an ecological setting that guid.